Environmental Ethics as a Question of Environmental Ontology Naess’ Ecosophy T and Buddhist Traditions - Cavazza, Elisa (2014)
Arne Naess included several references to Buddhist teachings in his ecophilosophy. I suggest an inquiry into and interpretation of the Buddhist sources of Naess’ proposal, in order to understand the role Buddhist elements play in it, and how they can offer a further understanding of central elements in Naess’ ecosophy. The focus is on the union of theory, worldview and practice, which lies at the core of both fields. A particular emphasis is placed on the idea that only a change of outlook on the nature of reality can promote an ethical transformation. In Naess’ approach, the ecological crisis is first of all a problem of our experience of the world, posing a question of ‘environmental ontology’. I suggest an hermeneutical approach primarily into early Indian Buddhist sources, and I argue that although a homogeneous ‘Buddhism’, as well as a ‘green Buddhism’ are problematic, different strands of thinking in Buddhist philosophy can facilitate the analysis of critical points also raised by Ecosophy T, supporting and expanding an ecosophical approach to ecological challenges.
Keywords: Buddhism; ecosophy; environmental ontology; Interdependence; Naess